The potential role of secondary metabolites in modulating the flavor and taste of the meat. (August 2019) - Ramalingam, Vaikundamoorthy; Song, Zhen; Hwang, Inho
Abstract: Flavor is one of the most significant characteristics of beef palatability and it can eventually affect the consumer's acceptance of a beef product and purchasing habits. Variation in beef quality is large and is due to many factors, such as differences in genetic background, sex, age, management and nutrition. The consumer's decision to purchase beef is guided by the perception of healthiness and a variety of sensory traits including color, tenderness, juiciness, and aroma or flavor. Apart from this, there are several factors including peptides, fatty acids, amino acids, vitamins, fat contents are also play a vital role in determining the taste and flavor of the meat. In this review, we try to explore and explain the potential role of these factors in modulating the flavor and taste of the meat in detail. Graphical abstract: Unlabelled Image Highlights: The novelty and significance of the work are as follows: Sensory properties of the meat. Effect of Maillard reaction in modulating the quality of the meat. Role of secondary metabolites in taste and flavor of the meat. Perception of the flavor in the meat quality.